Characterization of Doubled Haploid Derived from Anther Culture for New Type Upland Rice - Reny Herawati; Bambang Sapta Purwoko; Iswari S. Dewi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Anther culture is one of tissue culture methods which can be applied to plant breeding programs in order to accelerate the process of obtaining pure lines. The successful development of rice varieties is highly dependent on genetic diversity and desirable traits. To obtain the genetic variability of doubled haploid lines through anther culture techniques, anther F1 or F2 were used as explants sources. The objectives of the study were to select and characterize doubled haploid lines of upland rice having the characters of new plant type, and to study the genetic variability and agronomic characters of tested doubled haploid lines. A total of 58 doubled haploid lines, and four parental lines i.e. Fatmawati, SGJT-28, SGJT-36, and Way Rarem were used in this study. The experiment used completely randomized design with three replications. Results showed that the characters of the doubled haploid lines vary considerably. Selection of the character i.e. number of productive tillers, number of fi lled grain per panicle, and percentage of empty grain was more effective to be selected because they were well correlated to weight of grain per hill, possessed high heritability values, and have wide genetic variability. Based on productive tillers number, number of fi lled grains per panicle, fertility, weight of 1,000 grains, and weight of grains per hill, the lines of P3-26, P3-27, P3-28, P4-45, P5-50, P6-103, P6-105, P3-120, P3-134, P3-135, P3-150, P3-158, P3-248, P3-249, P6-271, P6-272, P6-274, P6-276, and P6-295 were potential for further selection for new type of upland rice.